How do you simplify (16 times r ^3 times t ^2) /(- 4 times r times t)?

Jan 15, 2017

See full simplification process below:

Explanation:

To simplify this expression use these rule for exponents:

${x}^{\textcolor{red}{a}} / {x}^{\textcolor{b l u e}{b}} = {x}^{\textcolor{red}{a} - \textcolor{b l u e}{b}}$

$a = {a}^{\textcolor{red}{1}}$

${a}^{\textcolor{red}{1}} = a$

(16 xx r^color(red)(3) xx t^color(red)(2))/(-4 xx r^color(blue)(1) xx t^color(blue)(1)

$- 4 \times {r}^{\textcolor{red}{3} - \textcolor{b l u e}{1}} \times {t}^{\textcolor{red}{2} - \textcolor{b l u e}{1}}$

$- 4 \times {r}^{2} \times {t}^{1}$

$- 4 \times {r}^{2} \times t$

Jan 15, 2017

$- 4 {r}^{2} t$

Explanation:

Using the $\textcolor{b l u e}{\text{law of exponents}}$

$\textcolor{\mathmr{and} a n \ge}{\text{Reminder }} \textcolor{red}{\overline{\underline{| \textcolor{w h i t e}{\frac{2}{2}} \textcolor{b l a c k}{{a}^{m} / {a}^{n} = {a}^{m - n}} \textcolor{w h i t e}{\frac{2}{2}} |}}}$

$\Rightarrow \frac{16 {r}^{3} {t}^{2}}{- 4 r t}$

$= \frac{16}{- 4} \times {r}^{3} / {r}^{1} \times {t}^{2} / {t}^{1}$

$= - 4 \times {r}^{3 - 1} \times {t}^{2 - 1} = - 4 {r}^{2} t$